2004
DOI: 10.1111/j.0014-3820.2004.tb01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Comparative Analysis of Life-History Variation Among Populations of the Lizard Sceloporus Undulatus:an Example and Prognosis

Abstract: Abstract. Over the past 15 years, phylogenetic comparative methods (PCMs) have become standard in the study of life-history evolution. To date, most studies have focused on variation among species or higher taxonomic levels, generally revealing the presence of significant phylogenetic effects as well as residual variation potentially attributable to adaptive evolution. Recently, population-level phylogenetic hypotheses have become available for many species, making it possible to apply PCMs directly to the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…In another lacertid lizard, Psammodromus algirus , two mt-DNA lineages differed in mean incubation time but not in offspring size, fecundity and maternal size (Díaz et al 2012). A weak effect of phylogeny on geographic variation of life-history traits was also reported for a widespread iguanian lizard, Sceloporus undulates (Niewiarowski et al 2004). In contrast, the variation in reproductive and other life-history traits among species of lacertid lizards included a substantial phylogenetic component (Bauwens and Díaz-Uriarte 1997).…”
Section: Discussionmentioning
confidence: 59%
“…In another lacertid lizard, Psammodromus algirus , two mt-DNA lineages differed in mean incubation time but not in offspring size, fecundity and maternal size (Díaz et al 2012). A weak effect of phylogeny on geographic variation of life-history traits was also reported for a widespread iguanian lizard, Sceloporus undulates (Niewiarowski et al 2004). In contrast, the variation in reproductive and other life-history traits among species of lacertid lizards included a substantial phylogenetic component (Bauwens and Díaz-Uriarte 1997).…”
Section: Discussionmentioning
confidence: 59%
“…However, whereas these variables were not significant to explain the genetic relationships among the groups, they suggested that both the phenotype and genotype were the results of independent processes (Haase and Misof 2009); that is, the microhabitat conditions had a great effect on the shell despite the existence of gene flow (Chiba and Davison 2007;Fiorentino et al 2013;Stankowski 2013;Proćków et al 2017). Thus, whereas it has been suggested that the use of comparative phylogenetic methods at intrapopulation levels may generate poor informative results (Niewiarowski et al 2004), the power of resolution of these methods may depend on the taxon and the assessed trait (Martins and Housworth 2002), as has been found in this study. In addition, our results suggested that populations with larger shells and apertures are distributed to the north, while populations with smaller shells and apertures were distributed to the south.…”
Section: Variation Of the Shell In H Durangoensismentioning
confidence: 99%
“…However, whereas these variables were not significant to explain the genetic relationships among the groups, they suggested that both the phenotype and genotype were the results of independent processes (Haase & Misof, 2009); that is, the microhabitat conditions had a great effect on the shell despite the existence of gene flow (Chiba & Davison, 2007;Fiorentino et al, 2013;Stankowski, 2013;Proćków, Kuźnik-Kowalska & Mackiewicz, 2017). Thus, whereas it has been suggested that the use of comparative phylogenetic methods at intrapopulation levels may generate poor informative results (Niewiarowski, Angilletta & Leaché, 2004), the power of resolution of these methods may depend on the taxon and the assessed trait (Martins & Housworth, 2002), as has been found in this study.…”
Section: Variation Of the Shell In H Durangoensismentioning
confidence: 99%